Formula for distance between two points:
d = √((x₂-x₁)² + (y₂-y₁)²)
Let point 1 be (-3, 11) and point 2 be (5, 5)
Therefore x₁ = -3, y₁ = 11, x₂ =5, y₂ = 5, and substituting in the formula above.
d = √((x₂-x₁)² + (y₂-y₁)²)
= √((5- -3)² + (5-11)²)
= √((5+3)² + (5-11)²)
= √((8)² + (-6)²) 8² = 8*8 = 64, (-6)² = -6*-6 = 36
= √(64 + 36)
= √(100)
= 10
Distance = 10 units.
Idk...........................................................................................
I = PRT
T = 6
P = 850
I = 1.9% = 0.019
I = (850)(0.019)(6) = 96.90 <==
34 divided by 14 is 2.42......
Then multiply it by 6 to get your Y.
that is what I think though, I may be wrong
To solve the given equation, you would need to multiply t by both terms inside the parenthesis.
The equation would be D. (t*14) - (t*5)